A multivariate analysis of comparative effects of heavy metals on cellular biomarkers of phytoremediation using Brassica oleracea. Issue 6 (11th May 2020) - Natasha,; Shahid, Muhammad; Saleem, Mazhar; Anwar, Hasnain; Khalid, Sana; Tariq, Tasveer Zahra; Murtaza, Behzad; Amjad, Muhammad; Naeem, Muhammad Asif
Abstract: The biochemical/physiological variations in plant responses to heavy metals stress govern plant's ability to phytoremediate/tolerate metals. So, the comparative effects of different types of heavy metals on various plant responses can better elucidate the mechanisms of metal toxicity and detoxification. This study compared the physiological modifications, photosynthetic performance and detoxification potential of Brassica oleracea under different levels of chromium (Cr), nickel (Ni) and selenium (Se). All the heavy metals induced a severe phytotoxicity to B. oleracea in terms of chlorophyll contents, Ni being the most toxic (76% decrease). Brassica oleracea showed high lipid oxidation: 87% and 273%, respectively in leaves and roots. Furthermore, all the metals increased the activities of catalase and peroxidase, while decreased superoxide dismutase and ascorbate peroxidase. Interestingly, heavy metals decreased hydrogen peroxide contents perhaps due to their possible transformation to another form of reactive oxygen species such as hydroxyl radical. Among the three metals, Ni was more phytotoxic than Cr and Se. Moreover, the phytoremediation/tolerance potential of B. oleracea to Ni, Cr and Se stress varied with the type of metal, their applied levels, response variables and plant organ type (root/shoot). The multivariate analysis separated different plant response variables and heavy metal treatments into different groups based on their correlations.